An interview study to determine the experiences of cellulitis diagnosis amongst health care professionals in the UK. Issue 10 (14th October 2020) - Patel, Mitesh; Lee, Siang Ing; Levell, Nick J; Smart, Peter; Kai, Joe; Thomas, Kim S; Leighton, Paul
Abstract : Objectives: To explore healthcare professionals (HCPs) experiences and challenges in diagnosing suspected lower limb cellulitis. Setting: UK nationwide. Participants: 20 qualified HCPs, who had a minimum of 2 years clinical experience as an HCP in the national health service and had managed a clinical case of suspected cellulitis of the lower limb in the UK. HCPs were recruited from departments of dermatology (including a specialist cellulitis clinic), general practice, tissue viability, lymphoedema services, general surgery, emergency care and acute medicine. Purposive sampling was employed to ensure that participants included consultant doctors, trainee doctors and nurses across the specialties listed above. Participants were recruited through national networks, HCPs who contributed to the cellulitis priority setting partnership, UK Dermatology Clinical Trials Network, snowball sampling where participants helped recruit other participants and personal networks of the authors. Primary and secondary outcomes: Primary outcome was to describe the key clinical features which inform the diagnosis of lower limb cellulitis. Secondary outcome was to explore the difficulties in making a diagnosis of lower limb cellulitis. Results: The presentation of lower limb cellulitis changes as the episode runs its course. Therefore, different specialties see clinical features at varying stages of cellulitis. Clinical experience is essential to being confident in making a diagnosis, but even among experienced HCPs, there were differences in the clinical rationale of diagnosis. A group of core clinical features were suggested, many of which overlapped with alternative diagnoses. This emphasises how the diagnosis is challenging, with objective aids and a greater understanding of the mimics of cellulitis required. Conclusion: Cellulitis is a complex diagnosis and has a variable clinical presentation at different stages. Although cellulitis is a common diagnosis to make, HCPs need to be mindful of alternative diagnoses.